Endemic mycoses: Expansion of traditional geographic ranges and pitfalls in management. Issue 9 (4th June 2021) - Thompson, George R.; Pasqualotto, Alessandro C.
Abstract: The endemic mycoses are a diverse group of environmental fungi that share several characteristics. Pitfalls in the recognition and management of endemic fungal infections are common. A general understanding of common presenting manifestations and their lingering effects is of paramount importance to the treating physician. We review the unmet needs of recently published guidelines and outline future areas of research.